2008 International Conference on Telecommunications 2008
DOI: 10.1109/ictel.2008.4652697
|View full text |Cite
|
Sign up to set email alerts
|

Resource allocation for the wire-tap multi-carrier broadcast channel

Abstract: Resource allocation for the multi-carrier broadcast channel is well understood for a broad class of utility functions, under various quality-of-service constraints, and for different channel models. In this work, we also take security on the physical layer into account. We use the secrecy rate as the objective function for resource allocation and show the similarities and differences to the traditional power and sub-carrier allocations for sum capacity optimization. The sub-carrier selection is similar for bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 12 publications
(17 reference statements)
1
62
0
Order By: Relevance
“…A great deal of studies have been devoted to informationtheoretic physical-layer security [1]- [5], In [1], [2], resource allocation for physical-layer security considerations was studied for multicarrier and multiple input multiple output (MIMO) systems. In [3], artificial noise was introduced in physicallayer security to obtain better performance in symmetric Gaussian interference channel.…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of studies have been devoted to informationtheoretic physical-layer security [1]- [5], In [1], [2], resource allocation for physical-layer security considerations was studied for multicarrier and multiple input multiple output (MIMO) systems. In [3], artificial noise was introduced in physicallayer security to obtain better performance in symmetric Gaussian interference channel.…”
Section: Introductionmentioning
confidence: 99%
“…The proof is based on the necessary Karush-Kuhn-Tucker (KKT) optimality conditions (Jorswieck & Wolf, 2008). Furthermore, it was shown that the remaining optimization problem…”
Section: Multi-carrier Systemsmentioning
confidence: 99%
“…In (Jorswieck & Wolf, 2008), it was shown that it is optimal to support only the best user per carrier. From that fact and the power constraint P A ℓ = P B ℓ + P E ℓ per carrier follows the user allocation per carrier, which is…”
Section: Wwwintechopencommentioning
confidence: 99%
“…The secrecy capacity of OFDM system was analyzed in the condition of eavesdropping end with different receiver in literature [2][3]. The literature [4] studied how the secrecy rate of OFDM system could reach the maximum through the reasonable power allocation. In [5], two practical physical layer security schemes for the MIMO orthogonal frequency-division multiplexing systems were proposed.…”
Section: Introductionmentioning
confidence: 99%